GOLPH3 Participates in Mitochondrial Fission and Is Necessary to Sustain Bioenergetic Function in MDA-MB-231 Breast Cancer Cells - Catalina M. Polanco; Viviana A. Cavieres; Abigail J. Galarza; Claudia Jara; Angie K. Torres; Jorge Cancino; Manuel Varas-Godoy; Patricia V. Burgos; Cheril Tapia-Rojas; Gonzalo A. Mardones (Cells, 2024)
In this study, we investigated the inter-organelle communication between the Golgi apparatus (GA) and mitochondria. Previous observations suggest that GA-derived vesicles containing phosphatidylinositol 4-phosphate (PI(4)P) play a role in mitochondrial fission, colocalizing with DRP1, a key protein in this process. However, the functions of these vesicles and potentially associated proteins remain unknown. GOLPH3, a PI(4)P-interacting GA protein, is elevated in various types of solid tumors, including breast cancer, yet its precise role is unclear. Interestingly, GOLPH3 levels influence mitochondrial mass by affecting cardiolipin synthesis, an exclusive mitochondrial lipid. However, the mechanism by which GOLPH3 influences mitochondria is not fully understood. Our live-cell imaging analysis showed GFP-GOLPH3 associating with PI(4)P vesicles colocalizing with YFP-DRP1 at mitochondrial fission sites. We tested the functional significance of these observations with GOLPH3 knockout in MDA-MB-231 cells of breast cancer, resulting in a fragmented mitochondrial network and reduced bioenergetic function, including decreased mitochondrial ATP production, mitochondrial membrane potential, and oxygen consumption. Our findings suggest a potential negative regulatory role for GOLPH3 in mitochondrial fission, impacting mitochondrial function and providing insights into GA–mitochondria communication.